MANAJEMEN SUMBER DAYA MANUSIA DALAM MEWUJUDKAN PEMBELAJARAN BERKUALITAS DI MADRASAH IBTIDAIYAH (MI) MA’ARIF NU 1 TUNJUNGMULI - ,, Fadlun (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2024)
This research aims to describe the planning, organization, implementation and control of human resources in realizing quality learning at the MI Ma’arif NU 1 Tunjungmuli. The approach used in this research is descriptive qualitative. The research location is at the MI Ma’arif NU 1 Tunjungmuli. In this research, the research subjects were the foundation chairs, boarding school leaders, all teachers, and madrasa committees. Research data was collected through in-depth interviews, participant observation, and document analysis. This research data was analyzed using interactive analysis techniques developed by Miles & Huberman, namely: data reduction, data presentation, and drawing conclusions. The results of the research show: (1) human resource planning in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli is carried out at the beginning of every year, always making a list of educators for the students; (2) organizing human resources in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli is carried out by holding meetings with educators, without any educational organization; (3) the implementation of human resources in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli has gone well because it is a routine; and (4) control of human resources in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli can be said to be quite good, control is also carried out by evaluating the human resources of the madrasa.